2022
DOI: 10.3390/ijms23126679
|View full text |Cite
|
Sign up to set email alerts
|

γH2AX, a DNA Double-Strand Break Marker, Correlates with PD-L1 Expression in Smoking-Related Lung Adenocarcinoma

Abstract: In recent years, the choice of immune checkpoint inhibitors (ICIs) as a treatment based on high expression of programmed death-ligand 1 (PD-L1) in lung cancers has been increasing in prevalence. The high expression of PD-L1 could be a predictor of ICI efficacy as well as high tumor mutation burden (TMB), which is determined using next-generation sequencing (NGS). However, a great deal of effort is required to perform NGS to determine TMB. The present study focused on γH2AX, a double-strand DNA break marker, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Consistently, the xeroderma pigmentosum group C protein complex and 8-oxoguanine DNA glycosylase-1 (OGG-1), two crucial proteins involved in nucleotide excision repair (NER) and DNA base excision repair (BER), respectively ( Tang et al, 2022 ), are upregulated in the exposed group. Interestingly, our data show no significant changes in the phosphorylation of histone H2AX at the Ser139 residue (γ-H2AX), early cellular responses of DNA double-strand breaks which is considered a biomarker for the toxicological risk assessment of tobacco products ( Sakurai et al, 2022 ). However, it was recently demonstrated that aldehydes such as formaldehyde can inhibit the activation of H2AX phosphorylation pathways ( Yang et al, 2019 ), and the chemical characterization of HnB mainstream smoke here reports that aldehydes are the chemical species with the highest concentration after nicotine.…”
Section: Discussionmentioning
confidence: 68%
“…Consistently, the xeroderma pigmentosum group C protein complex and 8-oxoguanine DNA glycosylase-1 (OGG-1), two crucial proteins involved in nucleotide excision repair (NER) and DNA base excision repair (BER), respectively ( Tang et al, 2022 ), are upregulated in the exposed group. Interestingly, our data show no significant changes in the phosphorylation of histone H2AX at the Ser139 residue (γ-H2AX), early cellular responses of DNA double-strand breaks which is considered a biomarker for the toxicological risk assessment of tobacco products ( Sakurai et al, 2022 ). However, it was recently demonstrated that aldehydes such as formaldehyde can inhibit the activation of H2AX phosphorylation pathways ( Yang et al, 2019 ), and the chemical characterization of HnB mainstream smoke here reports that aldehydes are the chemical species with the highest concentration after nicotine.…”
Section: Discussionmentioning
confidence: 68%
“…Based on these results, we hypothesized that LATS1/2 KO cells might harbor genome instability, resulting in a high TMB. Several reports showed that γH2AX, a marker of double-stranded DNA breaks, can be a marker of genome instability and positively correlates with TMB 25,26 . Remarkably, γH2AX was highly positive in LATS1/2 KO group but almost negative in WT tumors (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, another study superimposed two different IHC images by converting the DAB color into red and yellow colors, simulating double immunofluorescence. 4 In contrast, our technique decomposes an IHC image into RGB channels and converts it directly to a pseudoimmunofluorescent image.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that the IHC color intensity could be easily analyzed by focusing on yellow channel information; 3 however, no attempts were made to alter the color channels of the original IHC images. Additionally, another study superimposed two different IHC images by converting the DAB color into red and yellow colors, simulating double immunofluorescence 4 . In contrast, our technique decomposes an IHC image into RGB channels and converts it directly to a pseudoimmunofluorescent image.…”
Section: Discussionmentioning
confidence: 99%